Prevalence of zoonotic parasitic diseases of domestic animals in different abattoir of Comilla and Brahman Baria region in Bangladesh - Kabir, Md Hazzaz Bin; Eliyas, Mohammad; Hashem, Md Abul; Mohiuddin, M; Miazi, Omar Faruk (University Journal of Zoology, Rajshahi University, 2010)
A study was conducted to investigate about the prevalence of parasitic diseases in different abattoirs in selective area of Bangladesh such as Comilla and Brahmon Baria districts. Animals were examined for post-mortem defects in different abattoirs of those districts. The study started from February, 2008 to August, 2008. The total examined animals were 3510, among them 1460 cattle, 620 buffaloes, 970 goats and 460 sheep. Age, sex and breed of the examined animals were recorded as far as practicable. The overall prevalence of hydatidosis was highest (26.01%) followed by fascioliasis (20.74%), amphistomiasis (19.62%). The prevalence of above mentioned diseases was higher in older animals. The prevalence of hydatidosis, fascioliasis and amphistomiasis was higher in male in case of cattle and goats. But the prevalence of those diseases was distinctly higher in female animals in case of buffaloes and sheep. The proportional prevalence of different disease conditions in cattle was much higher in Hariana breed than those of local and crossbred cattle. Key Words: Abattoirs; zoonotic diseases; parasites; domestic animal. DOI: 10.3329/ujzru.v28i0.5281 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 21-25